The problem of constitutionality of the composition of the current National Council of the Judiciary in Poland - Skotnicki, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The National Council of the Judiciary was established in Poland in 1989 as a constitutional body. Her most important task is to safeguard the independence of the courts and the independence of judges. From the beginning, it is a mixed body composed of representatives of the legislative, executive and judicial powers dominated by judges. The 1997 Constitution established that this body consists of 25 members: the First President of the Supreme Court, the Minister of Justice, the President of the Supreme Administrative Court, a person appointed by the President of the Republic of Poland, fifteen members selected from among the Supreme Court judges, common courts, administrative courts and courts military members, four members elected by the Sejm from among deputies and two members elected by the Senate from among senators (Article 187 § 1). Therefore, the Constitution does not explicitly state that judges in the composition of the National Council of the Judiciary should be elected by judges. However, by the Constitutional Tribunal and the majority of representatives of the doctrine, this was derived from the principle of a democratic state ruled by law, the principle of the separation of powers, and the principle of the independence of the courts and the independence of judges. This was also the practice until 2017. At the time, based on the linguistic interpretation, it was considered that the judges in the National Council of the Judiciary could be elected by the Sejm, which was also done in 2018, while shortening the term of office of the current judges who are members of this body. This solution is criticized by the vast majority of the legal community, including the judicial one. This raised the question of whether the current composition of the National Council of the Judiciary is compatible with the Constitution. The author fully shares the view that this is not the case.